A bibliometric analysis of the impact of COVID-19 vaccines on the immune system (2020-2024) - Kurmangaliyeva , Saulesh S.; Madenbayeva, Akzhan M.; Urazayeva , Saltanat T.; Kurmangaliyev, Kairat B.; Bazargaliyev , Yerlan Sh.; Kudabayeva, Khatimya I.; Baktikulova, Kristina V. (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The rapid development and deployment of COVID-19 vaccines have been pivotal in mitigating the global pandemic, yet the long-term impact of these vaccines on the immune system remains an area of ongoing investigation. Methods: This bibliometric analysis aims to provide a comprehensive evaluation of global research trends and key findings related to the effects of COVID-19 vaccines on immune function, drawing on data from the Scopus and Web of Science Core Collection (WOS-CC) databases. Data merging, statistical analyses, and visualizations were conducted using RStudio and the Bibliometrix R package. Results: We analyzed 377 research and review articles published between 2020 and 2024, identifying trends in publication volume, citation metrics, and keyword frequency. Our findings highlight the complexity of vaccine-induced immunity, including the durability of immune responses, interactions with other vaccines, and potential alterations in immune surveillance. The analysis also underscores the importance of collaborative research efforts, with significant contributions from leading institutions and countries. Conclusions: This study offers valuable insights into the evolving landscape of COVID-19 vaccine research, emphasizing the need for continued investigation to optimize vaccination strategies and address emerging public health challenges.